Perspectives in the local software industry - De Veyra, Alfred John Anglo (College of Engineering, 1986)
"Perspectives in the Local Software Industry" describes the three general aspects of the software industry in the Philippines: the software companies, the software product and the environment and factors affecting the industry's existence. A description of the nature of activities of these companies, a survey of the application areas they engage in, and a discussion of the management concerns affecting planning and operations are all included to give a framework upon which an assessment of its nature, direction and the state of the technology may be made. The software product is discussed on the basis of whether these are custom-built or prepackaged. This difference is significant in terms of cost, development time and effort, marketing and return of investment because profitability is the concern of any company. Finally, a diverse picture of the environment, the status, the strengths and weaknesses of the industry and social and industrial considerations regarding development policies are presented. The differences in ideas and priorities represent a very interesting perception of the conditions and events that determine the future of the industry. Computer professionals give their own recommendations on how to make the industry's existence a better proposition for all concerned.